Advances in the Modelling of Thermodynamic Systems - Essefi, Elhoucine (IGI Global, 2022)
Thermodynamics is a common field of study involving many different specialties including physics, chemistry, geology, and cosmology. Thermodynamics is incredibly useful for manmade industrial processes related to material studies, renewable energy, and more. It is essential for professionals to stay current with the developments in thermodynamic systems, as thermodynamics proves vital for understanding natural macroprocesses related to geology, areology, and cosmology. Advances in the Modelling of Thermodynamic Systems discusses the recent advances in modeling of thermodynamic systems as well.